Predicting personalised remifentanil effect site concentration for surgical incision using the nociception level index: A prospective calibration and validation study. Issue 12 (21st December 2022) - Perrin, Laurent; Bisdorff, Max; Saxena, Sarah; Tabolcea, Ionut; Huybrechts, Isabelle; Van Obbergh, Luc; Engelman, Edgard; Barvais, Luc; Coeckelenbergh, Sean
Abstract : BACKGROUND: Inadequate antinociception can cause haemodynamic instability. The nociception level (NOL) index measures response to noxious stimuli, but its capacity to predict optimal antinociception is unknown. OBJECTIVE: To determine if NOL index change to a tetanic stimulus in cardiac and noncardiac surgery patients could predict the required remifentanil concentration for haemodynamic stability at skin incision. DESIGN: A prospective two-phase cohort study. SETTING: University hospital. PATIENTS: Patients undergoing remifentanil-propofol target controlled infusion (TCI) anaesthesia. INTERVENTIONS: During the calibration phase, investigators evaluated the tetanic stimulus induced NOL index change under standardised TCI remifentanil-propofol anaesthesia during a no-touch period [bispectral index (BIS) between 40 and 60, NOL index under 15]. If the NOL index change was 20 or greater following tetanic stimulation, investigators repeated the tetanus at higher remifentanil concentrations until the response was blunted. Surgeons incised the skin at this remifentanil concentration. The investigators derived a prediction model and in the validation phase calculated, using the NOL response to a single tetanus, the required incision remifentanil concentration for the start of surgery. MAIN OUTCOME: Haemodynamic stability at incision [i.e. maximum heart rate (HR) < 20% increase from baseline, minimum HR (40 bpm) and mean arterial pressure (MAP) ± <20% of baseline]. RESULTS: During the calibration phase, no patient had hypertension. Two patients had a HR increase slightly greater than 20% (25.4 and 26.7%) within the first 2 min of surgery, but neither of these two patients had a HR above 76 bpm. Two patients were slightly hypotensive after incision (MAP 64 and 73 mmHg). During the validation phase, neither tachycardia nor hypotension occurred, but MAP increased to 21.5% above baseline for one patient. CONCLUSION: During a no-touch period in patients under steady-state general anaesthesia [propofol effect site concentration (Ce) required for BIS between 40 and 60], the NOL index response to a tetanic stimulus under remifentanil antinociception can be used to personalise remifentanil Ce for the start of surgery and ensure stable haemodynamics. TRIAL REGISTRATION: ClinicalTrials.gov: NCT03324269